2018
DOI: 10.1097/md.0000000000011737
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcomes of fixed treatment of intravitreal aflibercept for exudative age-related macular degeneration and the factor of visual prognosis

Abstract: The aim of this study was to investigate the efficacy of periodic intravitreal aflibercept (IVA) in exudative age-related macular degeneration, and to explore the predictive factors for visual outcome.This is a prospective interventional case series.Fifty-two eyes of 52 treatment-naïve age-related-macula-degeneration patients were enrolled. All participants received IVA bimonthly following 3 monthly loading dose. The primary endpoint was change in best corrected visual acuity (BCVA) and central retinal thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…This agrees with other studies where the authors showed that the MS measured by MP improved up to 6 or 12 months during aflibercept therapy. Ono et al [35] reported that the BCVA was significantly improved at 3, 6, and 12 months relative to the baseline after IVA, which is similar to our findings. Moreover, the changes in the retinal sensitivity in a 10° macular area measured by MAIA perimetry were significantly improved at 12 months relative to the baseline but not at 6 months.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This agrees with other studies where the authors showed that the MS measured by MP improved up to 6 or 12 months during aflibercept therapy. Ono et al [35] reported that the BCVA was significantly improved at 3, 6, and 12 months relative to the baseline after IVA, which is similar to our findings. Moreover, the changes in the retinal sensitivity in a 10° macular area measured by MAIA perimetry were significantly improved at 12 months relative to the baseline but not at 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…Because of these features, the application of MP in clinical studies has provided important diagnostic and prognostic information on the functional macular changes in AMD patients [27]. The information collected by MP in the functional assessment of nAMD is helpful, and it can quantify the severity of the functional depression at various stages of AMD [28,29], investigate the relationship between the retinal sensitivity and the retinal morphology [30,31], and determine the efficacy of anti-VEGF agents (bevacizumab [32], ranibizumab [33], and aflibercept [34][35][36]). However, the studies that have reported the changes in retinal sensitivity in patients with nAMD during aflibercept treatments are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation